Propriedades vibracionais de cristais de L-valina a altas temperaturas e a altas pressões - Silva, João Hermínio da (2007)
In this work the vibrational properties of an amino acid crystal, the L-valine – one of the molecules constituents of proteins in animals, was investigated under extreme conditions of temperature and pressure. The description was made separating it into two parts: In the first, the behavior of the normal modes of the crystal L-valine is described in the temperature range comprised between 24 to 150oC. The results allowed to establish the stability of the original monoclinic structure in the complete temperature range studied. Also, the linear coefficients, dω/dT, were obtained from the ωvs T plots, where ω stands for the wave number, for all normal modes observed. With this data it is possible to obtain the explicit contribution representing the change in the occupation of phonons. In the second part, the description of the evolution with pressure varying be tween 0 and ~7 GPa, is furnished for all normal modes of the L-valine crystal. The ove rall results, including the spectral region for the external modes and those for internal modes, lead to some singular observations: (i) Relevant changes were observed in all spectral regions in the Raman spectrum when the pressure attains the value ~ 3 GPa, in increasing the pressure; (ii) Severe changes are observed in some spectral ranges when the pressure attains ~5.3 GPa in increasing the pressure. The ωvs P plots undergo sudden and strong discontinuities for both pressure values, probed by changes in slope or disapp earance of some lines with appearance of others. In particular, at the highest energy spectral region, st rong changes of intensity are observed at those pressure values. At ~3 GPa the intensity of the spectrum is seen to increase by about a factor of 5 times and at ~5.3 GPa the in tensity decrease. Those changes indicate the crystal structure to be affected by the externally applied pressure, inducing phase transitions. As the spectral region between 2850 and 3100 cm-1 contains the CH stretching modes, it is possible that the CH bond is modified by the transitions, causing a rearrangement of the molecules in the unit cell. Taking into consideration that the intensity increase at 3 GPa and decrease at 5.3 GPa, there is a possibility that th e bond is stiffened at the lower pressure and softened up at the higher, affecting, therefore, the intensity. A molecular rearrangement can occur with no chan ge in the crystal symmetry. However, other spectral regions were also affected at thos e pressures, making the change in symmetry a iv more credible consideration. To analyze further, consider, for instance, the spectral region between 320 and 600 cm -1, where the NCC- deformations, the vibrations associated with the skeletal structure, and NH 3 torsion vibrations occur. The ω vs P discontinuities observed for this spectral region at 3 GPa indicates that all those vibratio nal modes were affected by the pressure, thus reinforcing the structural phase transition hypotheses. At this point, it is fundamental to call attention to the split ting of the band 17, which correspond to a CO 2 - rocking, at about 1.8 GPa that is a completely isolated event. A possible explanation is the increase in the intermolecula r interaction due to the d ecrease of spacing among the molecules induced by the applied pressure. The intermolecular interaction increase can cause the splitting of internal modes, as previ ously observed for the Taur ine crystal, with no change being produced in the crystal structure. This effect can account well enough for the band 17 splinting at ~1.8 GPa. In the spectral region between 600 and 1200 cm -1 the Raman bands are weak and their disappearance should not be taken as a si gn for phase transition. Next region, betw een 1400 and 1700 cm -1 , is characteristic of the following types of vibration: CH 3 symmetric deformation, corresponding to the lines positioned at 1399 and 2428 cm -1 (lines numbered as 33 and 34); CH 3 asymmetric deformations occurring at 1449 and 1454 cm -1 (lines 35 and 36); CN stretching at about 1510 cm -1 (line 37); NH 3 asymmetric deformation at 1639 cm -1 (line 39). Line 34 is di scontinuous at 5.3 GPa, and could not be observed for higher pressures due to a superposition with its neighbor at 1453 cm -1 . Line 35 is discontinuous due to a splitting occurring at 3 GPa. Li ne 39 is discontinuous at 3 GPa, because it can not be observed for pressu re above this value. Therefore, a series of other vibrations than those of the higher energy region ar e affected by pressure, and constitute a stronger evidence for the crystal structure to change at 3 and 5.3 GPa.